Analisis radiograf periapikal menggunakan software imageJ pada abses periapikal setelah perawatan endodontik - Dominica Dian Saraswati Sumantri; Ria Noerianingsih Firman; A. Azhari (Majalah Kedokteran Gigi Indonesia, 2017)
Periapical abscess radiography analysis using imageJ after endodontics treatment. The visual assessment to measure the lesion of periapical abscesses on the radiograph interpretation has the distinction of periapical in intra observer and inter observer which caused by the subjectivity of observer. The assessment on abscess periapikal after endodontic treatment commonly has been seen visually from the reduced size of the lesion periapical abscess. On this research, the measurement of periapical abscesses lesion is done with measuring the number of particles, the extensive of lesions, and the extensive of particle on the radiograph after endodontic treatment on digitally. The purpose of this research is to knowing the extensive of lesions, the number of particles and the extensive particles of trabeculae bones after endodontic treatment on periapical abscess through digitization periapical radiograph using ImageJ software. This research have a form of observational analysis. Samples was taken as many as 31 on each radiograph before and after treatment of endodontic patients with diagnosis of periapical abscess at RSGM Padjadjaran University Bandung. The radiograph will digitized using ImageJ software to get the extensive of lesions, the number of particles and the particle of extensive in periapical abscess. The results of this research found that of the 31 pairs of radiograph before and after endodontic treatment there is decrease in the average area of lesions from 12.44 ± 2.29 mm2 into 2.72 ± 1.86 mm2, increase in the average number of particles of 56.22, to 79.61, an increase in the average particles area of 8.93 ± 2.55 mm2, being 11.42 ± 2.61 mm2. The summary of this research is there is a decrease in the size of the lesions, which are affected by the increase in the number of particulate matter and particles on the radiograph of the extensive of lesions periapical abscess after endodontic treatment.ABSTRAKPenilaian secara visual pada abses periapikal pada radiograf periapikal, memiliki perbedaan interpretasi secara intra dan inter observer yang diakibatkan subjektitas penilaian. Penilaian pada abses periapikal setelah perawatan endodontik secara visual umumnya dilihat dari berkurangnya ukuran abses periapikal. Pada penelitian ini pengukuran abses periapikal dilakukan dengan mengukur luas lesi, jumlah partikel, dan luas partikel pada radiograf setelah perawatan endodontik secara digital. Tujuan penelitian ini untuk mengetahui luas lesi, jumlah partikel dan luas partikel trabekula tulang setelah perawatan endodontik pada abses periapikal melalui digitalisasi radiograf periapikal menggunakan software ImageJ. Penelitian bersifat analisis observasional. Sampel diambil sebanyak masing-masing 31 radiograf sebelum dan setelah perawatan endodontik pasien dengan diagnosa abses periapikal di RSGM Universitas Padjadjaran Bandung. Radiograf di digitalisasi menggunakan software ImageJ untuk mendapatkan hasil luas lesi, jumlah partikel dan luas partikel abses periapikal. Hasil penelitian ditemukan bahwa dari 31 pasang radiograf sebelum dan setelah perawatan endodontik terdapat penurunan rata-rata luas lesi dari 12,44 ± 2,29 mm2 menjadi 2,72 ± 1,86 mm2, peningkatan rata- rata jumlah partikel dari 56,22 buah, menjadi 79,61 buah, peningkatan rata-rata luas partikel dari 8,93 ± 2,55 mm2, menjadi 11,42 ± 2,61 mm2. Simpulan penelitian ini adalah analisis radiograf abses periapikal menggunakan software imageJ ditemukan penurunan ukuran luas lesi, yang dipengaruhi oleh kenaikan jumlah partikel dan luas partikel setelah perawatan endodontik.